Narasi Islam dalam Studi Orientalisme dan Post Kolonialisme - Aik Iksan Anshori (The International Journal of Pegon : Islam Nusantara civilization, 2021)
Abstract This paper will try to uncover the affair of orientalism and (post) colonialism in which the orientalist discourse, at the practical level, cannot be separated from the intertwined network of colonialism. In fact, between the two there is a reciprocal relationship that is so intimate in the form of cultural hegemony of orientalism which is fully supported by the authority of colonialism or vice versa, depending on the frame of the object being studied. But the first option is more appropriate to be my choice--for the sake of adaptation of the basic theme that will be raised. This lengthy presentation, aside from presenting paradoxical historical accounts between the two—in fact, each has its own historical identity—it will also strip down the motivation, background and epistema of the two. And with a little rash, because of my limitations, it can also be said as a case study of both at once. Tulisan ini akan mencoba menguak perselingkuhan orientalisme dan (post) kolonialisme dimana wacana orientalis, dalam tataran praksis, tidak bisa dilepaskan dari jejaring kolonialisme yang bererat-kelindan. Bahkan antar keduannya ada hubungan timbal balik yang begitu mesra berupa hegemoni kebudayaan orientalisme yang disokong penuh oleh otoritas kekuasaan kolonialisme atau bisa juga kesebalikannya, bergantung frame objek yang dikaji. Namun opsi yang pertama lebih tepat jadi pilihan saya--demi adaptasi dari tema dasar yang akan diangkat. Paparan panjang ini, disamping akan mempresentasikan paparan-paparan sejarah yang paradoks antar keduanya—bahkan sejatinya masing-masing memiliki ciri identitas sejarah sendiri—pun juga akan mempreteli motivasi, latar belakang dan epistema keduannya. Dan dengan sedikit gegabah, karena keterbatasan saya, bisa dikatakan pula sebagai studi kasus keduanya sekaligus.